Supersets for the spectrum of elements in extended Banach algebras - Morteza Seddighin (International Journal of Mathematics and Mathematical Sciences)
If A is a Banach Algebra with or without an identity, A can be always extended to a Banach algebra A¯ with identity, where A¯ is simply the direct sum of A and C, the algebra of complex numbers. In this note we find supersets for the spectrum of elements of A¯.